Applicability of the Dix-Hallpike test on benign paroxysmal positional vertigo: literature review - Silva, Geraedson Aristides da; Gomes, Jessiane Carneiro; Teixeira, Geraldo Magella; Santos, Clistenis Clênio Cavalcante dos; Santos, Almira Alves dos (Journal of Health & Biological Sciences, 2019)
Objective; to analyze the applicability of the Dix-Hallpike maneuver on BPPV as a diagnostic method for the semicircular canals as well as its sensitivity. Methods: a literature review was performed using the following sourcing databases: LILACS, PubMed, SCIELO looking forpapers published in Portuguese, English and Spanish. The following searching strategy descriptors were used: vertigo, vestibular diseases and respiratory therapy techniques, being included publications between the years 2000 and 2017. Results: the results of the work were presented through a synoptic table and flowchart. Conclusion: There is still controversy regarding its sensitivity to the anterior and lateral canals, even if the maneuver, does not present sensitivity of 100%, its level of closeness provides security in the diagnosis of BPPV.